ANALISIS KEMANDIRIAN EMOSIONAL PADA PESERTA DIDIK KELAS VIII MADRASAH TSANAWIYAH NEGERI 2 PONTIANAK - Emi Idayanti; Yuline Yuline; Purwanti Purwanti (Universitas Tanjungpura, 2020)
ABSTRACTEmotional autonomy is adolescents' ability to free themselves by de-idealizing their parents, self-reliance, and responsibility. These aspects involved: emotional autonomy of self-duty, biological basis, and psychological basis. Therefore, the researcher would like to find out deeper regarding the emotional autonomy of class VIII students in Madrasah Tsanawiyah Negeri 2 Pontianak. This research's problem is,